Guía práctica para la aplicación del estándar ohsas 18001:2007 en la empresa centro acero s.a - Saldarriaga Viteri, Lady Diana (2011)
The present work is developed in the company Centro Acero S.A., it is dedicated to the development and delivery of steel manufacturing. The General Objective is to realize a practical guide for the implementation of OHSAS 18001:2007 in the company, in order that the language used is easily understood by people who want to implement it. The methodology used is the Standard OHSAS 18001:2007 and it is also based on the Deming Cycle, PHVA; which consists on: planning objectives and processes, implement processes, monitoring and measurement of results and taking actions for continues improvement. The initial diagnosis realized to the company was made in relation to the requirements of the rule in order to make the practical guide aligned to the business of the company. And finally the conclusions and recommendations indicated.